Relevance of Omega-3 and Omega-6 / Omega-3 Ratio in Preventing Cognitive Impairment - Nunes, Belina (2017)
Introduction: The epidemiological and social relevance of dementia and mild cognitive impairment increases with life expectancy and prevalence of metabolic disorders. The recognition of an important role for dietary nutrients on cognitive functioning opens new preventive strategies. This work analyses the association between erythrocyte omega-3 index and omega-6 / omega-3 ratio and cognitive performance/ mild cognitive impairment.Material and Methods: We selected a random sample of individuals registered at a health centre aged ≥ 55 years. Participants were asked about their alimentary habits, erythrocyte indexes were determined and neuropsychological evaluation included the Montreal Cognitive Assessment and a comprehensive test battery.Results: Mean age of 90 participants was 64 years (sd = 5.6), 71.1% had four years of education and 40% of them had more than one vascular risk factor. Limits for omega-3 index and omega-6 / omega-3 ratio were 2.90 - 9.79 (mean = 6.20; sd = 1.50) and 1.14 - 2.95 (mean = 2.12; sd = 0.39), respectively. Montreal Cognitive Assessment scores ranged from 10 to 29 (mean = 22; sd = 4.5), increasing on average 1 - 2 points for above average omega-3 values and an omega-6 / omega-3 ratio ≤ 2 (Group 1) and decreasing 5 - 6 points for omega-3 below mean values and the same omega-6 / omega-3 ratio (Group 2). Prevalence of mild cognitive impairment was 25.6% (95% CI: 16.4 - 34.7), ranging from 12.5% to 83.3% in the two groups above.Discussion: This preliminary study is one of the first analyzing the repercussion of omega-3 index and omega-6 / omega-3 ratio on cognitive functioning, considering additionally the participant clinical and dietary profiles.Conclusion: The association found suggests that omega-3 and omega-6 / omega-3 ratio could be important biomarkers in the prevention of cognitive impairment.